THE FORMULATION OF SUNSCREEN CREAM FROM TELANG FLOWER EXTRACT (CLITOREA TERNATEA) AND IN VITRO TESTING OF SUN PROTECTION FACTOR (SPF) VALUE - pramushinta, Intan ayu kusuma; ajiningrum, Purity sabila (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. Telang flower contains chemical compounds such as flavonoids that have the pharmacological potential as an antioxidant. The flavonoid compounds in plants are assumed to have antioxidants and the ability to protect the skin from UV rays. Method. This research method used a descriptive-analytic approach. The sampling of telang flowers was conducted in the greenhouse garden of the Biology Study Program, Faculty of Science and Technology, PGRI Adi Buana University, Surabaya. Result&Analysis.The research stages include the process of extracting flowers by maceration method, the process of microemulsion system from telang flower extract, microemulsions characterization, SPF values testing on microemulsion of telang flower extract and statistical data analysis. Discussion. Based on the table of multiple comparison test results in formulation 0 with hypotheses 1, 2 and 3 having a p-value of <0.05, it can be interpreted that there are differences in each formulation. However, there is no difference between formulation 1 and hypothesis 4 which has a p-value of> 0.05.